Fatty Acid Composition and Toxicity of Melia azedarach L. Fruits against Malaria Vector Anopheles stephensi: Composition of Melia azedarach fruits and its effect on Anopheles stephensi - Hadjiakhoondi, Abbas; Vatandoost, Hassan; Khanavi, Mahnaz; Sadeghipour-Roodsari, Hamid Reza; Vosoughi, Mohsen; Kazemi, Motahareh; Abai, Mohammad Reza (Iranian Journal of Pharmaceutical Sciences, 2006)
The fruit of Melia azedarach L. (Meliaceae) was extracted with hexane, and its fatty acids methyl ester was analyzed using GC/MS. Thirteen components representing 85.1% of the total extract were identified. The major components identified were methyl palmitate (18.8%), methyl linolenate (16.1%) and methyl linoleate (9.8%). The fruits’ extract had a LC50 of 5.5 ppm against the larvae of Anophles stephensi.